The Cascading Helix: A three-dimensional conceptual model aimed at improving organizational communication and performance - J. Raddall (South African Journal of Business Management, 1984)
This article introduces the Cascading Helix as a three-dimensional dynamic, conceptual model which represents formal and informal relationships in an organization. The Helix replaces the traditional two-dimensional static model which has been used for decades. It is suggested that this latter model has become inadequate to represent real world conditions that exist in the eighties. The Helix can be used by companies as a practical model. Employees' names can be attached hierarchically to the Helix which can move from steady state to inversion and back to steady state. This dynamic process introduces an Important concept, i.e. the benefits of shared strategic responsibility. Strategic decision-making is not the sole domain of top management. Each employee has a contribution to make in determining the direction of the company. Certain topics, important to a firm's survival are also discussed. These include informal communication, values and culture, organizational control, conflict resolution and strategic management. In this article it is suggested that the Cascading Helix can be used as an educational tool in these areas to bring about necessary changes in the organization's philosophy and behaviour.Hlerdie artikel stel die Dinamiese Spiraal (Cascading Helix) as 'n driedimensionele dinamiese begripsmodel bekend, wat formele en informele verhoudings binne 'n organisasie verteenwoordig. Die spiraal vervang die tweedimensionele, statiese model wat al vir dekades in gebruik is. Dit blyk dat die model nie langer werklike wereldtoestande van die tagtigerjare weerspieel nie. Maatskappye kan die spiraal as 'n praktiese model gebruik. Werknemers se name kan hierargies aan die spiraal gekoppel word, en die spiraal kan beweeg van 'n stabiele staat tot die omgekeerde, en weer terug na stabiel. Die dinamiese proses stel 'n belangrike begrip bekend, naamlik die voordele van gemeenskaplike strategiese verantwoordelikheid. Die topstruktuur het nie meer alleenreg op strategiese besluitneming nie. Elke werknemer kan 'n bydrae lewer tot die bepaling van die rigting van die maatskappy. Sekere onderwerpe wat belangrik is vir 'n maatskappy se voortbestaan word ook bespreek. Dlt sluit informele kommunikasie, waardes en kultuur, organisatoriese beheer, konflikoplossing en strategiese bestuur in. In hierdie artikel word daar voorgestel dat die dinamiese spiraal gebruik kan word as opleidingswerktuig op hierdie gebiede, om die nodige veranderlnge in die organisasie se beleid en optrede te bewerkstelllg.
Keywords: 650